Tangeretin attenuates bleomycin-induced pulmonary fibrosis by inhibiting epithelial-mesenchymal transition via the PI3K/Akt pathway - Li, Jiang; Wei, Qian; Song, Ke; Wang, Youxin; Yang, Yuxin; Li, Miao; Yu, Jiaying; Su, Guangxu; Peng, Luyuan; Fu, Bendong; Yi, Pengfei (Frontiers in Pharmacology, 2023)
Pulmonary fibrosis (PF) is a terminal pathological change in a variety of lung diseases characterized by excessive deposition of extracellular matrix, for which effective treatment is lacking. Tangeretin (Tan), a flavonoid derived from citrus, has been shown to have a wide range of pharmacological effects. This study aimed to investigate the role and potential mechanisms of Tan on pulmonary fibrosis. A model of pulmonary fibrosis was established by administering bleomycin through tracheal drip, followed by administering Tan or pirfenidone through gavage. We found that Tan significantly ameliorated bleomycin-induced pulmonary fibrosis, improved fibrotic pathological changes, and collagen deposition in the lungs, and reduced lung inflammation and oxidative stress. The RNA sequencing was conducted to investigate the alterations in gene expression in mouse lung tissue subsequent to drug administration. The KEGG pathway enrichment analysis revealed a higher number of enriched genes in the PI3K/Akt pathway. Additionally, it was discovered that Tan had inhibitory effects on the epithelial-mesenchymal transition (EMT) process, which is associated with pulmonary fibrosis. Taken together, Tan suppresses inflammation, oxidative stress, and EMT in BLM-induced pulmonary fibrosis via the PI3K/Akt pathway and is a potential agent for the treatment of pulmonary fibrosis.